Research Progress on the Production and Regulation Mechanism of Spicy Sensation - WANG Zixuan, WANG Tongtong, WANG Min, HAN Tianlong, LIU Dengyong (Shipin Kexue, 2023)
Capsaicin is the source of spicy taste in pepper fruits. Capsaicin stimulates nerve endings and reacts with some molecules to produce bioelectric pulses, which trigger the transient receptor potential vanilloid 1 (TRPV1) channal in human nerves, and then transmit the signal to the brain to produce a spicy feeling. It is found that capsaicin synergizes with or inhibits taste, and the interaction between them varies depending on the concentration of capsaicin. Therefore, this paper summarizes the types, chemical properties and applications of capsaicinoids, describes the biological mechanism by which capsaicin causes a spicy sensation, namely activating the capsaicin receptor TRPV1 channel, and discusses the interaction of spiciness with sour, sweet and bitter taste. Next, this review points out the shortcomings of the current research on the interaction between spiciness and taste and the potential underlying mechanism, and provides an outlook on future research directions. It is expected that this review will provide theoretical support for the further development of the spicy foods industry.